Direct Macrophage to NK Cell Lipid Transfer; A New Concept in NK Cell Regulation - Keane, Cathal (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2026)
Natural killer (NK) cells are innate, cytotoxic lymphocytes that kill virally infected and transformed cells, as well as exerting direct bactericidal activity. Their ability to quickly kill their targets in the absence of antigen recognition makes them a favourable option for the development of immunotherapies. Understanding the metabolic requirements of NK cells is essential to achieve optimal responses of NK cell-based therapies. Current understanding of NK cell metabolism is based on studies of cultured NK cells in isolation and has provided a lot of information on their fuel preferences and metabolic regulators. For example, sterol regulatory element-binding proteins (SREBPs) have been shown to be important to support glucose metabolism in NK cells following activation. The SREBP target genes Slc25a1 and Acly in particular are essential to support NK cell glycolysis and OxPhos through a non-canonical TCA cycle, called the citrate malate shuttle (CMS). However, in complex tissue niches, there is dynamic interplay between NK cells and other cells in the environment. These extrinsic signals have the potential to shape NK cell metabolism, leading to alterations in their effector function. Macrophages are innate, phagocytic myeloid cells that have wide ranging functions depending on the environment they are found in. They are found ubiquitously, meaning they are constantly interacting with other immune cells. Following LPS-stimulation, macrophages have been shown to produce an oxidised derivative of cholesterol called 25-hydroxycholesterol (25HC). Many oxysterol species, including 25HC have important roles in controlling cellular lipid homeostasis through inhibiting the activation of SREBP transcription factors. It has been shown that oxysterols can inhibit NK cell metabolism and effector functions in response to cytokine stimulation through inhibition of SREBP, though data in this report also highlights that they have other SREBP-independent inhibitory effects on NK cells through modulating plasma membrane structure. Therefore, it was hypothesised that macrophages could limit NK cell metabolism and effector functions through their production of 25HC. While data in this thesis shows that LPS-stimulated macrophages can limit NK cell effector responses, this was independent of any changes in levels of 25HC. It was shown that direct contacts between NK cells and LPS-stimulated macrophages dampened IFN production by NK cells. Analysis of other metabolic parameters revealed that in the presence of LPS-stimulated macrophages, cultured NK cells adopt a metabolic configuration that involves lipid storage, an effect which is not seen in NK cells cultured in isolation. This was characterised by an increase in lipid droplet number in NK cells and increased expression of genes involved in handling fatty acids. The increase in lipid accumulation was mirrored in vivo with peritoneal NK cells increasing their lipid content following LPS-immunisation. Direct contacts with macrophages were also required for NK cells to express the lipid scavenging receptor CD36, which was hypothesised to be required for lipid uptake and storage by NK cells. While it was shown that the lipid accumulation in NK cells was not dependent on CD36-mediated uptake of exogenous fatty acids, the use of macrophages deficient in CD36 revealed that NK cells were obtaining this protein from macrophages through trogocytosis, rather than endogenous expression. Given that CD36 can be transferred from macrophages to NK cells through trogocytosis, it was hypothesised that NK cells could also be obtaining lipids from macrophages through a similar mechanism. The use of pharmacological inhibitors of lipid synthesis revealed that lipid accumulation in NK cells is dependent on de novo fatty acid synthesis by LPS-stimulated macrophages. The de novo synthesised fatty acids are then transferred to the NK cells through direct contacts. Using an irreversible inhibitor of fatty acid synthase to specifically block de novo fatty acid synthesis in macrophages, resulted in a rescue in IFN production by co-cultured NK cells. This reveals a novel metabolic communication axis between macrophages and NK cells that can control NK cell IFN production. Given the role of IFN in activating macrophages, this may represent a negative feedback mechanism to limit sustained stimulation of macrophages and prevent progression to hyperinflammatory conditions such as sepsis.
APPROVED
Keywords: Natural killer cells; Macrophages; Immunometabolism; Intercellular communication; Fatty acids; Lipids; Interferon gamma